Made in Barcelona - Climate adapted urban design for manufacturing - Ekander Swanberg,Assar (2025)
Transforming our economy from linear to circular requires new types of businesses in the manufacturing sector, material flows change from global to local. Our cities need to make room for manufacturing again, to repair, upcycle, design, make, resell, and produce local solutions. This presents an urban design challenge, how does a manufacturing area fit in to the climate adapted city needed to reduce our emissions and handle a changing climate? Torrent d’Estadella, a small scale and diverse industrial area on the edge of central Barcelona is seeing transformation around it. A new train station, linear park and design university will soon be Estadella’s neighbors, changing its position within the city dramatically. It has potential to be transformed into a showcase of climate adapted urban design that facilitates urban manufacturing, a crucial tool to realize circular production. Intensified industrial space, shared yards, green streets, cultural spaces and more presents a new vision of what a manufacturing area can be. The proposed design makes room for new manufacturing space alongside complementary uses that promote the creation of a circular economy and activate the area during more hours of the day. Repair centers, recycling facilities, material banks and design centers can work together in close proximity to make Estadella a hub for the sustainable economy of making in Barcelona. New connections and a logistical network improve the connectivity to Estadella making it an integrated part of the city, both for everyday workers and residents and the local supply chains that facilitate Barcelona’s shift towards a circular economy. Green streets and small parks provide everyday greenery and shading, an inviting environment that promotes soft mobility, cools down the city and creates spaces for everyday breaks. Estadella will welcome people to manufacture a sustainable future for Barcelona.
Keywords: Urban Design; Barcelona; Sustainability; Architecture; Industrial; Manufacturing; Density; Climate adaptation; Typologies; Public space